Enforcer or Enabler? Rethinking the Kimberley Process in the Shadow of Marange - Mtisi, Shamiso (Weaver Press, 2021)
Enforcer or Enabler? Rethinking the Kimberley Process in the Shadow of Marange Shamiso Mtisi Introduction The Kimberley Process (KP) Certification Scheme, an international agreement established in 2003 to regulate the rough diamond trade, is sometimes held up as a leading example of how diverse interests can co-operate globally for the common goal of development and peace. However, ten years after its founding, the KP’s uneven record underscores its complex, ambiguous character as an international organisation increasingly influenced by powerful interests that stand against its founding objectives of transparency, fairness and the upholding of rights in the diamond trade. Nowhere is this seen more clearly than in the case of the KP’s handling of Marange diamonds after 2006. Rather than enforcing global standards of best practice in the extraction and marketing of Marange’s stones, the KP often served as an enabler of practices that violated its own core principles and practices. How was the KP knocked off track in its engagement with Zimbabwe – and which forces within it have fought to ensure that justice and 68 Facets of Power development are consolidated in Marange’s diamond fields? How has a small number of actors come to manipulate the organisation for self-interested ends – and what can be done to democratise and bring greater transparency to the KP and its practices? This chapter provides an insider ’s perspective on the KP in addressing these and related questions. It is grounded in the author’s experience as a member of the KP civil society coalition, including five years of participating in KP meetings, deliberations, country monitoring and other activities in Zimbabwe, and around the world. From this standpoint, the KP displays both important strengths and potential, and worrying weaknesses and possible pitfalls. The Marange story brings both sets of characteristics into stark relief, and raises critical questions within and outside the KP about its viability and pathways to reform. It demonstrates how an embattled government and certain powerful politicians within it can work successfully to fan conflict among KP members, deliberately trampling upon the tripartite and consensual nature of the organisation and undermining its core monitoring functions, to ensure the trade in tainted diamonds proceeds undeterred . At the same time, Marange also reveals the limitations of the KP more broadly, and provides a context for the growing calls for the organisation’s reform and revision in order to meet the challenges of the rough diamond trade in the twenty-first century. The discussion begins with an account of the KP’s basic structure, rules and processes, and Zimbabwe’s first engagement with the scheme. It then focuses on the emergence of Marange as a point of contention among the organisation’s key tripartite forces, including the Zimbabwean government, other government signatories to the scheme, industry and civil society. The ebbs and flows and distorting effects of conflicts among these actors is charted through an account of the difficult and controversial meetings, missions and negotiations involving the prohibition of rough diamond exports from Marange – and the conditions for its lifting. The concluding section reflects on the KP’s strengths and weaknesses, and identifies lessons learnt from the Marange debacle that perhaps point to a new way forward for the KP. Throughout, the challenges, advances and opportunities for civil society’s contribution to the renewal of the KP remain an important point of concern. 69 Enforcer or Enabler? Rethinking the Kimberley Process PM Tsvangirai, Minister Mpofu and senior government officials touring Anjin in 2012 Mechanised mining at Anjin in 2012 70 Facets of Power The Kimberley Process Certification Scheme and Zimbabwe: Institutions and interests The KP Certification Scheme is the main global governance institution for regulating the trade of rough diamonds. It is a tripartite organisation which brings together diamond producing and consuming country governments , the diamond industry and civil society organisations working on rights and minerals, and was founded in line with several United Nations Security Council and General Assembly Resolutions.1 Its primary objective was to eliminate the trade of ‘conflict diamonds’. For the KP, which was partly inspired by the key financing role of diamonds in the violent civil conflicts of Sierra Leone and Angola, the definition of conflict diamonds focused on stones exploited by rebel movements and their allies to finance their fights against legitimate governments. Under the KP, a certification scheme was set up to exclude conflict diamonds from the legitimate trade. This works via internal systems of controls enacted through national laws which...